FACTORS AFFECTING CARBON EMISSION DISCLOSURE: GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Jaenudin Jaenudin; Endang Ruhiyat; Sugiyanto Sugiyanto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
This study examines the influence of green strategy, green investment, and environmental performance on carbon emission disclosure, with good corporate governance as a moderating variable. The research adopts a quantitative approach using secondary data. The research method employed is documentation, with data collected from annual and company sustainability reports. The sample in this study consists of non-financial companies listed on the Indonesia Stock Exchange from 2020 to 2022, using a purposive sampling method. The sample obtained includes 91 companies out of a population of 772 companies. The data analysis technique used in this study is multiple linear regression analysis. The results show that the variables of green strategy and environmental performance have a positive influence on carbon emission disclosure, while green investment does not affect carbon emission disclosure. In the MRA testing, good corporate governance does not moderate the relationship between green strategy and environmental performance with carbon emission disclosure. In contrast, good corporate governance weakens the relationship between green investment and carbon emission disclosure.